The interaction of polyhydroxyalkanoate polymer group with cells and tissues - Maiborodin, I.V.; Kuznetsova, I.V.; Shevela, A.I.; Manaev, A.A.; Chastikin, G.A. (Вiopolymers and Cell, 2014)
In the recent literature devoted to the results of the study, formulation and application of polyhydroxyalkanoates (PHA), contains a wealth of experimental and clinical data on efficacy and safety of using these polymers with biomedical goals. However, the application of PHA, both independently and in combination with other drugs and substances that must surely have its advantages and disadvantages. It should be noted the complete absence, information on contraindications and complications of the PHA, and insufficient data on the patterns of degradation of PHA in vivo, and morphological processes connected with it of scientific literature.